2009
DOI: 10.2353/jmoldx.2009.080098
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Circulating Plasma DNA Levels between Lung Cancer Patients and Healthy Controls

Abstract: Although the biological functions of tumor-originated cell-free DNA have not been previously clarified , such molecular characteristics as mutations , hypermethylation , and microsatellite instability have confirmed its tumor origin. Therefore , to investigate the use of plasma DNA level as a biomarker of lung cancer, we compared plasma DNA concentrations in 102 patients with lung cancer and 105 healthy individuals using quantitative PCR analyses. The median plasma DNA concentrations for the healthy and cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(74 citation statements)
references
References 15 publications
4
70
0
Order By: Relevance
“…Thus, circulating plasma cell-free DNA (CFDNA) may, in theory, represent tumor burden or tumor biologic aggressiveness, regardless of the releasing mechanisms. A series of studies has shown that lung cancer patients have higher levels of CFDNA in the blood compared with healthy controls (7)(8)(9). However, the prognostic or predictive value of circulating plasma CFDNA for the treatment outcomes and survival of lung cancer patients remains controversial (9)(10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, circulating plasma cell-free DNA (CFDNA) may, in theory, represent tumor burden or tumor biologic aggressiveness, regardless of the releasing mechanisms. A series of studies has shown that lung cancer patients have higher levels of CFDNA in the blood compared with healthy controls (7)(8)(9). However, the prognostic or predictive value of circulating plasma CFDNA for the treatment outcomes and survival of lung cancer patients remains controversial (9)(10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…For example, lung cancer cases have significantly more serum-derived DNA than controls (p < 0.0001). 25 In non-small cell lung cancer patients, Esteller et al showed that when a patient's tumor was positive for methylation (at one of four investigated genes) 73% of the time methylated DNA was also detectable in the serum. 26 Other work in lung cancer has been similar: in 2002, An et al showed that 88% of patients (n = 64/73) with CDKN2A methylation in tumors also had methylation in serum-derived DNA.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, in a recent study, CTCs captured on the aptamer‐functionalized SiNWs substrates were distinguished from non‐specifically trapped WBCs by using a three‐color immunological method based on FITC‐labeled anti‐EpCAM, Cy5‐labeled anti‐CD45, and DAPI nuclear staining 117. Most CTCs molecular identification methods use DNA testing techniques such as polymerase chain reaction (PCR) and restriction fragment length polymorphism (RFLP) to analyze the specific DNA or mRNA of CTCs enriched 117, 118. PCR‐based analysis technique are the most widely used molecular method for CTCs detection and identification.…”
Section: Approaches For Ctc Detection and Identificationmentioning
confidence: 92%
“…For example, in size filtration‐based microfluidic system with microcavity arrays, two fluorescent immunological probes of FITC‐labelled anti‐CD45 antibody and PE‐labelled anti‐EpCAM antibody were employed to detect and identify CTCs captured on the microcavity arrays 59. Similarly, in a recent study, CTCs captured on the aptamer‐functionalized SiNWs substrates were distinguished from non‐specifically trapped WBCs by using a three‐color immunological method based on FITC‐labeled anti‐EpCAM, Cy5‐labeled anti‐CD45, and DAPI nuclear staining 117. Most CTCs molecular identification methods use DNA testing techniques such as polymerase chain reaction (PCR) and restriction fragment length polymorphism (RFLP) to analyze the specific DNA or mRNA of CTCs enriched 117, 118.…”
Section: Approaches For Ctc Detection and Identificationmentioning
confidence: 99%